1977
DOI: 10.1111/j.1469-1809.1977.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age effect in Down's syndrome

Abstract: Increasing incidence of Down's syndrome with advancing paternal age for given maternal age has been demonstrated. Comparisons are made between an almost complete Down's syndrome sample from the Copenhagen Metropolitan Area and a randomly selected sample of births from the same area and the same time period. Men above 55 years have a significantly increased risk of getting children with Down's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 16 publications
3
32
1
1
Order By: Relevance
“…Table 3 shows the distribution of paternal age in DS subjects with respect to karyotype. A significantly increased incidence of Down syndrome was reported in the children of Danish men over 55 years of age by Stene et al (1977). Similar findings were reported by Matsunaga et al (1978) for Japanese men and by Erickson and Bjerkedal (1981) in the Norwegian population.…”
Section: Resultssupporting
confidence: 78%
“…Table 3 shows the distribution of paternal age in DS subjects with respect to karyotype. A significantly increased incidence of Down syndrome was reported in the children of Danish men over 55 years of age by Stene et al (1977). Similar findings were reported by Matsunaga et al (1978) for Japanese men and by Erickson and Bjerkedal (1981) in the Norwegian population.…”
Section: Resultssupporting
confidence: 78%
“…The findings on the impact of parental ages at childbearing on the incidence of congenital anomalies vary somewhat from study to study; for example, while most studies have found no effect of the father's age on Down syndrome, a few studies have shown an effect (e.g., Stene et al 1977;Stene et al1981). This is probably because the number of children born with a congenital anomaly is small compared to the number of children born without such abnormalities, and because the ages of the mother and the father tend to be strongly correlated.…”
Section: Discussionmentioning
confidence: 98%
“…Recent observations have demonstrated an increase in the rate of autosomal recessive disorders among the progeny of men 35 years of age and older [7], [8] . These findings suggest an agerelated decline in gamete quality among men, albeit one that is more subtle than that experienced by women [2] .…”
Section: Discussionmentioning
confidence: 99%